HASIL BELAJAR KETERAMPILAN PROSES IPA SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN TERPADU DI KELAS VII A3 MTs DAR EL HIKMAH PEKANBARU - M. Rahmad; Mursyidah Mursyidah; Mitri Irianti (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2008)
The purpose of this research has described learning result of physics science skill process byapplying integrated learning model to first year students MTs Dar El Hikmah Pekanbaru on topic object,motion, and microscope. This research involved an experiment research. The subject of this research wasfirst year students MTs Dar El Hikmah Pekanbaru at academic year 2007/2008 in totally 32 student. Thetechnique of collecting data by using test of physics science skill process. The technique of data analysis byusing descriptive analysis. Data analysis showed that abortive power is 74 % with good category, learneffectiveness can be categorized in effective enough, but completeness of student’s learns is not complet.Hence, integrated learning model is effective enough to first year students MTs Dar El Hikmah Pekanbaruon topic object, motion, and microscope.Key words : integrated learning model, learning result, skill process